The fiery heart - Mead, Richelle (New York : Razorbill, an imprint of Penguin Group (USA), 2013)
After making a life-changing decision, Sydney Sage, an Alchemist who serves to bridge the worlds of humans and vampires, must tread a careful path as she harnesses her profound magical ability to undermine the way of life she was raised to defend.
Includes an excerpt from'Vampire Academy.'
Keywords: Alchemists -- Juvenile fiction; Vampires -- Juvenile fiction; Alchemists -- Fiction; Vampires -- Fiction